Trinuclear cyanido-bridged MII-WV complexes (M = Mn, Co): Crystal structures and magnetic properties. (1st July 2022) - Dragancea, Diana; Novitchi, Ghenadie; Madalan, Augustin M.; Alexandru, Maria-Gabriela; Shova, Sergiu; Andruh, Marius
Graphical abstract: Abstract: Two new trinuclear heterometallic complexes, [{Mn II (L)(CH3 OH)}2 {W V (CN)8 }](NO3 )·CH3 OH·H2 O (2) and [{Co II (L)(CH3 OH)}2 {W V (CN)8 }](NO3 )·CH3 OH·H2 O (3 ), have been assembled from mononuclear cationic modules, [M(L)(H2 O)2 ] 2+, and [W(CN)8 ] 3– as a metalloligand (M = Mn II ; Co II, L is the pentadentate ligand resulting from the condensation reaction between 2, 6-diacetylpyridine and semicarbazide). The crystal structure of the manganese(II) precursor, [Mn II (L)(H2 O)2 ](NO3 )2 ·H2 O 1, and of the trinuclear compounds 2 and 3 have been solved. Within the three compounds the 3d metal ions show a pentagonal bipyramidal coordination geometry. The magnetic properties of compounds 2 and 3 have been investigated. Compound 2 shows an irregular spin state structure with S  = 9/2 arising from Mn II -W V antiferromagnetic interactions ( J  = −8.00 cm −1, H  = -2 J S 1 S 2 ). In compound 3, the Co II -W V exchange interaction was found ferromagnetic ( J  = +12.3 cm −1 ).